PERMASALAHAN TATA RUANG KOTA DI TANGERANG: ANALISIS KONFLIK ANTARA KEPADATAN PENDUDUK DAN RUANG HIJAU - Dian Rahmah Fajarida (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
Effective urban spatial planning is a key element in supporting sustainable urban development. Tangerang, as one of the rapidly growing urban areas, faces significant challenges due to conflicts between increasing population density and the need for green spaces as ecological balancing elements. This study aims to analyze the issues of urban spatial planning in Tangerang, focusing on the factors driving the conflict between population density and the provision of green spaces. A qualitative approach was used, involving secondary data analysis from urban spatial planning documents, government policies, and relevant literature reviews.The findings indicate that high urbanization rates, discrepancies in the implementation of spatial planning policies, and low public awareness of the importance of green spaces are the primary factors exacerbating the problem. Additionally, the lack of green spaces has negative impacts on environmental quality, such as rising urban temperatures, increased flooding, and a decline in residents' quality of life. As a solution, this study recommends integrating spatial planning strategies based on ecological approaches, including optimizing zoning policies, developing vertical gardens in densely populated areas, and enhancing community participation in green space conservation. These findings are expected to contribute to more sustainable urban spatial planning in Tangerang and other cities facing similar challenges.